Marc Chagall - Dallmayr, Fred R. (Fred Reinhard), 1928- author.
1 online resource (xii, 69 pages)
Keywords: "This book follows Chagall's life through his art and his understanding of the role of the artist as a political being. It takes the reader through the different milieus of the nineteenth and the twentieth century - including the World Wars and the Holocaust - to present a unique understanding of Chagall's artistic vision and peace in an age of extremes. At a time when all identities are being subsumed into a 'national' identity, this book makes the case for a larger understanding of art as a way of transcending materiality. The volume explores in Chagall's work the Platonic notions of truth, goodness, and beauty are linked and mutually illuminating. A "spiritual-humanist" interpretation of his life and work renders Chagall's work more transparent and accessible to the general reader. It will be essential reading for students of art and art history, political philosophy, political science, and peace studies"--